2015
DOI: 10.1049/el.2015.2394
|View full text |Cite
|
Sign up to set email alerts
|

Compact tri to dual passband switchable bandpass filter using stub‐loaded split‐ring resonator with improved bandwidth

Abstract: Stub-loaded split-ring resonators (SRRs) are presented for the design of a compact tri-to dual-band bandpass filter (BPF). The length of the two concentric split-rings having splits on the opposite sides, the gap between the two concentric split-rings and the length of the stub determine the positions of the three passbands. Switchability has been achieved by controlling the closing and opening of the inner ring of the SRRs using pin diodes. The responses of the BPF depend upon the condition of the switch. Mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…Hence, the curves in the right part of Fig. 3 are created by (4), while (6) have no result in this part. The left part means u < u R , which is in accordance with (6a).…”
Section: Voltage-null Point Of the Third Harmonic Frequencymentioning
confidence: 99%
See 2 more Smart Citations
“…Hence, the curves in the right part of Fig. 3 are created by (4), while (6) have no result in this part. The left part means u < u R , which is in accordance with (6a).…”
Section: Voltage-null Point Of the Third Harmonic Frequencymentioning
confidence: 99%
“…Hence, the curves in the left part of Fig. 3 are created by (6), while (4) has no result in this part.…”
Section: Voltage-null Point Of the Third Harmonic Frequencymentioning
confidence: 99%
See 1 more Smart Citation
“…Multi-frequency micro-strip filters are required to effectively pick up the signals of each separate frequency band and prevent signal crosstalk between adjacent channels, which requires higher frequency selectivity and out-of-band rejection of the filters [4][5][6]. In recent years, scholars in various countries have carried out in-depth research and proposed various design methods to solve the two core problems in the design of multi-band micro-strip filters [14][15][16][17][18][19][20]: Firstly, multi-point frequency selection can be realized, multi-frequency can work in parallel, and each central frequency point has a certain capacity bandwidth; secondly, the signals in adjacent frequency bands must be effectively isolated and can not interfere with each other, and the out-of-band rejection performance of the filter is reliable. There are two main methods for designing multi-band filters [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35]: Firstly, based on the combination of multi-band filters, including the cascade of broadband filters and notch filters, and the parallel connection of multiple filters in different frequency bands; secondly, based on the parasitic frequency of resonators, a multi-band filter is designed.…”
Section: Introductionmentioning
confidence: 99%
“…In past, many research works have been reported to achieve switchable responses in radio-frequency (RF) filters [1][2][3][4][5][6][7][8][9]. Switchable bandpass filter (BPF) with dual-state frequency behaviour based on grounded stub-loaded resonator is reported in [1], in which switching of the first passband is independently controlled using the PIN diode connected between the resonator and the loaded grounded stub.…”
Section: Introductionmentioning
confidence: 99%